Stem Cell–Derived Retinal Pigment Epithelial Layer Model from Adult Human Globes Donated for Corneal Transplants. (26th April 2018) - Fernandes, Marie; McArdle, Brian; Schiff, Lauren; Blenkinsop, Timothy A.
Abstract: An adult human retinal pigment epithelial layer (ahRPE) model derived from stem cells isolated from native RPE monolayers (ahRPE‐SCs) exhibits key physiological characteristics of native tissue and therefore provides the means to create a human "disease in a dish" model to study RPE diseases. Traditionally, RPE lines are established from whole globes dedicated to research. Here we describe a new technique for establishing primary RPE lines from the posterior poles of globes used for corneal transplants. Since tissues from corneal transplants are derived from younger and healthier donors than those used for research, we have hypothesized that RPE cells isolated from corneal transplantation globes will result in improved primary RPE line establishment. Our new procedure increases the rate of establishing successful RPE cultures and improves the total cell number yield. Use of this advanced methodology can provide a new source of high‐quality primary RPE line cultures. © 2018 by John Wiley & Sons, Inc.